2003
DOI: 10.1073/pnas.1735526100
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of mouse aortic smooth muscle cells to a macrophage-like state after cholesterol loading

Abstract: Mouse aortic smooth muscle cells (SMCs) were loaded for 72 h with cholesterol by using cholesterol:methyl-␤-cyclodextrin complexes, leading to Ϸ2-fold and Ϸ10-fold increases in the contents of total cholesterol and cholesteryl ester, respectively. Foam-cell formation was demonstrated by accumulation of intracellular, Oil Red O-stained lipid droplets. Immunostaining showed decreased protein levels of smooth muscle ␣-actin and ␣-tropomyosin and increased levels of macrophage markers CD68 and Mac-2 antigen. Quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
414
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 435 publications
(461 citation statements)
references
References 40 publications
25
414
1
2
Order By: Relevance
“…Regulation of progenitor cell differentiation is a complex process, dependent on numerous hormones, growth factors, and specific activation of a cascade of gene expression [42,[46][47][48][49][50][51].Critical regulators of adipocyte differentiation include C/EBPα (CCAAT/enhancer binding protein), PPARγ2 (peroxisome proliferator-activated receptor), and LPL (lipoprotein lipase) [47,48,[52][53][54][55][56][57]. Alternatively, transdifferentiation of smooth muscle cells into other phenotypes may occur [58][59][60][61]. Inhibition of 5α-reductase activity induces stromal remodeling and smooth muscle dedifferentiation in the prostate, suggesting that 5α-DHT deficiency promotes smooth muscle dedifferentiation [62].…”
Section: Testosterone Regulates Cellular Growth and Differentiationmentioning
confidence: 99%
“…Regulation of progenitor cell differentiation is a complex process, dependent on numerous hormones, growth factors, and specific activation of a cascade of gene expression [42,[46][47][48][49][50][51].Critical regulators of adipocyte differentiation include C/EBPα (CCAAT/enhancer binding protein), PPARγ2 (peroxisome proliferator-activated receptor), and LPL (lipoprotein lipase) [47,48,[52][53][54][55][56][57]. Alternatively, transdifferentiation of smooth muscle cells into other phenotypes may occur [58][59][60][61]. Inhibition of 5α-reductase activity induces stromal remodeling and smooth muscle dedifferentiation in the prostate, suggesting that 5α-DHT deficiency promotes smooth muscle dedifferentiation [62].…”
Section: Testosterone Regulates Cellular Growth and Differentiationmentioning
confidence: 99%
“…Excessive cholesterol accumulation in cells leads to the formation of foam cells, which is one of the hallmarks of atherosclerotic plaques within the arterial wall. In a previous study [31] , we successfully established a foam cell model by using 10 μg/mL Chol:MβCD, which is "water-soluble cholesterol" containing approximately 50 mg of cholesterol per g of solid (molar ratio, 1:6 cholesterol:MβCD) that delivers cholesterol rapidly and directly to the plasma membrane [32] . Using Oil Red O staining, we determined the morphological changes in cells after incubation of VSMC with Chol:MβCD in the absence or presence of 3 μmol/L ezetimibe for 72 h. Our results showed that ezetimibe treatment dramatically reduced cellular lipid accumulation in VSMCs treated with Chol:MβCD (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The cells were then loaded with FC/cyclodextrin (Sigma) (molar ratio, 1:6 cholesterol/M␤CD), 20 g/ml, in serum-free media. After 24 h of loading, cells were equilibrated for 12 h and then fixed in 4% paraformaldehyde in PBS and stained with Oil Red O (Sigma) for neutral lipids (24).…”
Section: Methodsmentioning
confidence: 99%